SHARIA DIGITAL BUSINESS : STRATEGI DAN PENGEMBANGAN BISNIS BERKELANJUTAN - Nugraha, Aryan Eka Prastya; Murniawaty, Indri (EQUILIBRIUM, 2018)
The purpose of this study is to introduce strategies and develop digital businesses on an ongoing basis that remain Islamic based to be able to continue to compete in the current era of digital disruption. The methods used are Literature review papers (LRPs). The results of the study explain that there are several appropriate strategies to be used as a reference for digital sharia business, namely products sold, product promotion, alternative payments that are in accordance with rules and do not violate religious prohibitions (riba, gharar, maysir, and haram). The development of the right strategy of the selected sharia products must be precisely in accordance with market demand. The pricing strategy that is set must also meet the requirements, namely the need for openness from the seller to the buyer, which is explained in detail the price components on the online trading platform, or on the online marketplace. The sustainability of the digital sharia business sector in the next few years is a matter of great interest, and this research can be used as a reference for strategies to continue to survive and develop.